In and Out of the Homosexual Closet: Gay/Lesbian Liberation in Canada - Kallen, Evelyn (Culture, 1986)
With a substantive focus on Canada, this paper analyzes the sequential social processes involved in the movement for Gay/Lesbian liberation from a human rights perspective. In Phase One (Into the Closet), the paper examines the process of stigmatization of homosexuals whereby their minority status is socially created, institutionalized and perpetuated. In Phase Two (Out of the Closet), the paper examines the processes of destigmatization and “Coming Out” whereby a new and positive sense of collective, homosexual identity is generated. In Phase Three (Minority Liberation), the paper traces the evolution of homosexual organizations, from the early stage of self-help groups, through Gay/Lesbian Rights organizations seeking legal recognition and protection of the human rights of homosexuals, to the current movement for Gay/Lesbian Liberation seeking legitimation for the alternate lifestyles and sub-cultures of the Gay/Lesbian social collectivity.